Application of Parametric Modeling in the Calculation of the Flow Rate of Cycloidal Pump - Chen Wenjie; Zou Min; Zhu Hailin; Wang Zhiyang (Jixie chuandong)
To solve the problems that theoretical flow calculation of cycloidal rotor pump is complicated and the accuracy of empirical formula is low,the parametric modeling technique is introduced into the calculation of the flow rate of cycloidal pump based on Creo / parametric. The parametric model of the end face of the pump chamber is established. And the displacement of the pump is calculated by establishing the measurement characteristic. By comparison with theoretical displacement,the conclusion that the accuracy of the parametric model is higher than the empirical formula is verified. According to the integral principle,the accumulation model of the change of the cavity surface in the meshing movement is established. By sensitivity analysis,The curve of the cavity end face change rate to the rotor movement angle is established. And the flow curve is obtained. By comparison with theoretical flow curve,the correctness of the curve is verified.